The Bible: A Very Short Introduction - Riches, John (New York Oxford University Press, 2000)
This Very Short Introduction looks at the importance accorded to the Bible by different communities and cultures and attempts to explain why it has generated such a rich variety of uses and interpretations. It explores how the Bible was written, the development of the canon, the role of Biblical criticism, the appropriation of the Bible in high and popular culture, and its use for political ends.
Includes Index and Illustrations.
Keywords: Bible -- Introductions